Protecting children during child protection research using administrative data - Jade Hooper; Linda Cusworth; Helen Whincup (International Journal of Population Data Science, 2019)
Background with rationale Child protection systems aim to protect children from harm. Child protection research shares the same goal. However, the process of undertaking this research can present a risk. For child protection research using administrative data, children and families are at risk through breaches of privacy and identification, and further ethical issues of fair and necessary processing. This can be particularly challenging for countries such as Scotland, where smaller communities may mean children and families are more easily identifiable. For researchers and data gatekeepers alike, it is our duty to protect children in every way that we can throughout the process.